Optogenetic Stimulation Enhanced Neuronal Plasticities in Motor Recovery after Ischemic Stroke - Changbo Lu; Xianglong Wu; Hongzhe Ma; Qingchuan Wang; Yikai Wang; Yan Luo; Cong Li; Hui Xu (Neural Plasticity)
Motor capability recovery after ischemic stroke involves dynamic remodeling processes of neural connectomes in the nervous system. Various neuromodulatory strategies combining direct stimulating interventions with behavioral trainings for motor recovery after ischemic stroke have been developed. However, the effectiveness of these interventions varies widely due to unspecific activation or inhibition of undefined neuronal subtypes. Optogenetics is a functional and structural connection-based approach that can selectively activate or inhibit specific subtype neurons with a higher precision, and it has been widely applied to build up neuronal plasticities of the nervous system, which shows a great potential in restoring motor functions in stroke animal models. Here, we reviewed neurobiological mechanisms of enhanced brain plasticities underlying motor recovery through the optogenetic stimulation after ischemic stroke. Several brain sites and neural circuits that have been previously proven effective for motor function rehabilitation were identified, which would be helpful for a more schematic understanding of effective neuronal connectomes in the motor function recovery after ischemic stroke.